Pricing strategy for Pestana Collection and Pestana CR7 in Madrid: group part A - Fonseca, Marta (2021)
The underlying project aims to achieve a pricing strategy of two Hotels of Pestana Group, from two different brands – Collection and CR7 – that will be placed in Madrid. Thus, this work project centres on an analysis of the Madrid market with a posterior analysis of the con-sumer profile of each brand and respective competitors prices. Finally, for a successful inter-nationalization a pricing entry strategy is suggested and supported by a revenue model that each hotel unit is expected to face in the first year.